Gambaran Penggunaan Obat Golongan Narkotika dan Psikotropika di Rumah Sakit X - Indra Mukti; Rita Septiana; Khotimatul Khusna (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2024)
Narcotics and Psychotropics were substances that were managed with strict laws by the government. Based on a survey by the National Narcotics Agency (BNN) and the Indonesian Institute of Sciences (LIPI), 2.3 million students in Indonesia have consumed narcotics. This study aims to see the types of narcotic and psychotropic drugs given to outpatients at Hospital X, Sragen Regency. This study was a descriptive study, research data was taken from outpatient medical records. The sample in this study were outpatients aged 18-60 years, receiving narcotic and oral psychotropic drugs with complete medical record data. The results of the study showed that most of the patients were female at 75%, the largest age group in the range of >25-45 years at 47%, the most common diagnosis was coronary heart disease at 81%, and the most common main complaint was muscle pain and cramps at 50%. The type of narcotic drugs given to patients at hospital x in Sragen district was codeine at 19%, while the types of psychotropic drugs that were often given were opineuron 46%, analsik 27% and alprazolam 8%. For further researchers, it is necessary to evaluate the use of narcotic and psychotropic drugs.